2006
DOI: 10.1261/rna.2302706
|View full text |Cite
|
Sign up to set email alerts
|

RNA-associated protein 55 (RAP55) localizes to mRNA processing bodies and stress granules

Abstract: The mRNA processing body (P-body) is a cellular structure that has an important role in mRNA degradation. P-bodies have also been implicated in RNAi-mediated post-transcriptional gene silencing. The objective of this study was to identify and characterize novel components of the mammalian P-body. Approximately 5% of patients with the autoimmune disease primary biliary cirrhosis have antibodies directed against this structure. Serum from one of these patients was used to identify a cDNA encoding RAP55, a 463-am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
141
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(155 citation statements)
references
References 31 publications
12
141
0
2
Order By: Relevance
“…LSm14A was originally discovered to be a component of the Pbodies (18). Our study demonstrate that LSm14A is a sensor for both viral RNA and DNA and acts as a switch point on viral RNA-and DNA-induced IFN pathways, respectively.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…LSm14A was originally discovered to be a component of the Pbodies (18). Our study demonstrate that LSm14A is a sensor for both viral RNA and DNA and acts as a switch point on viral RNA-and DNA-induced IFN pathways, respectively.…”
Section: Discussionmentioning
confidence: 65%
“…In the present study, we identified a component of the processing bodies (P-bodies), LSm14A (also called RAP55), as an activator of IRF3 in expression screen experiments (18). Our results indicated that LSm14A bound to synthetic or viral RNA and DNA and was essential for initiating the induction of IFN-β in the early phase of virus infection.…”
mentioning
confidence: 67%
See 3 more Smart Citations